The behavior of II-A isotherm with increasing amount of calix[4] arene at airwater interface - Azhari N. A., Supian F. L., Abd Karim M. M. (N/A, 2014)
The behavior of II-A isotherm with increasing amount of calix[4] arene at airwater interface by Azhari N. A., Supian F. L., Abd Karim M. M.,